Genetic relatedness among cyprinids inferred by cytochrome b - Moghaddam, Faezeh Yazdani; Daud, Siti Khalijah; Siraj, Siti Shapor; Panandam, Jothi Malar; Aliabadian, Mansour (2009)
Puntius is a genus belonging to the family Cyprinidae, the most widely distributed freshwater fish all over the world. There are confusions in the taxonomic status of this genus whereby the classification of this genus is based solely on the morphological characteristics. Thus, the present study highlighted the phylogenetic relationships among common cyprinids found in Peninsular Malaysia. Fifty samples of Puntius and other genera were collected from different locations in Peninsular Malaysia, namely Sungai Pahang, Sungai Perak, Banting (Selangor) and Langkawi. Two mitochondrial Cyt b primers, namely Cyto 1 and Cyto 2, were used in this study. The average pairwise distance between all Puntius was 0.151 while the average value for cyprinids was 0.109. Based on cytochrome b gene, all species of Puntius can reasonably be regarded as different species. The phylogenetic tree revealed that Puntius is paraphyletic genus because different species of Puntius did not cluster to each other. Therefore, the revision of this genus is needed in the near future.